SHORT-TERM EFFECTS OF THE COMPLEX REHABILITATION PROGRAM INCLUDING NEMEC’S CURRENTS AND THERAPEUTIC EXERCISES IN PATIENTS WITH KNEE OSTEOARTHRITIS - Galina Мratskova; Nedko Dimitrov; Alexandеr Dimitrov; Petya Goycheva; Damyan Petrov (Science & Research)

(untitled)
The purpose of this study is to evaluate the short-term therapeutic effects of treatment with Nemec’s medium-frequency currents and therapeutic exercises in patients with knee osteoarthritis. Material and methods: The study included 54 patients with symptomatic osteoarthritis of the knee joints, II and III radiological degrees on the Kellgren-Lawrence scale with a mean age of 65.4±9.9(40-85), who conducted rehabilitation with Nemec’s currents and therapeutic exercises. All patients underwent a ten-day rehabilitation course. The results were evaluated by manual muscle testing test (MMT), measuring the circumference of the knee joint (KJ) with centimeter, test range of motion (Goniometry), pain (VAS), WOMAC Index, before and immediately after therapy. The statistical significance of the changes is p<0.05. Results: A statistically significant decrease in the circumference of KJ after therapy (p<0.05), reduction of muscle weakness m. Quadriceps by MMT test (p<0.05), reduction of pain (VAS) at rest and activity (p<0.05) and WOMAC Index (p<0.05) and increase in the range of flexion in the knee joint (p<0.05) was observed. Conclusion: The results of the study showed significant improvement in the functional activity of patients (WOMAC Index). Nemec’s medium frequency currents therapy and therapeutic exercises can effectively reduce pain (VAS), swelling, muscle weakness (MMT), and range of motion in patients (ROM) with gonarthritis. The obtained therapeutic effects are probably based on the complex application of Nemec’s current in trophic and analgesic parameters and therapeutic exercises.